A case series of heriditary spastic paraplegia (Panacea Journal of Medical Sciences, 2025)
Hereditary spastic paraplegia is a spectrum of disorders with progressive spasticity of lower limbs with clinical and genetic heterogeneity. Harding classified HSP into pure and complicated forms. Currently classification is largely based on genetics. Around 87 genetic loci were identified till date. We have studied 44 patients presented with spastic ataxia with or without additional neurologic or non-neurological features from February 2021 to February 2024. Out of 44 spastic ataxia cases studied over period of 3 years, 17 patients were positive for SPG genes with 21 variants detected by NGS method. New phenotypic representation of SPG 28 as it can present with spastic paraparesis and distal upper limb amyotrophy, i.e., Silver Syndrome. We found SPG 11 to be the most common inherited cause of hereditary spastic paraplegia in our study. SPG 7 is next common HSP type found. In conclusion, SPG 11 should be tested in cases presenting with spastic paraparesis before second decade, with thin corpus callosum, ear of lynx on MRI along with other neurological features like cognitive decline. With gene specific therapy on the horizon diagnosing HSP cases based on NGS should be considered.